Odpowiedź :
{1/2x-3/4y=0 /*12
{2/3x+ 1¼ y=9/*12
{6x - 9y = 0 /:3
{8x + 15y = 108 /:4
{2x - 3y = 0
{2x = 27 - 3,75y
{27 - 3,75y - 3y =0
{2x = 27 - 3,75y
{y=4
{x=6
{2/3x+ 1¼ y=9/*12
{6x - 9y = 0 /:3
{8x + 15y = 108 /:4
{2x - 3y = 0
{2x = 27 - 3,75y
{27 - 3,75y - 3y =0
{2x = 27 - 3,75y
{y=4
{x=6
1/2x - 3/4y = 0 |: 1/2
2/3x + 1¼y=9
x= 3/2y
2/3(3/2y) + 5/4y=9
x=3/2y
y+5/4y = 9
x= 3/2y
9/4y = 9 |: 9/4
x=2/3y
y=4
x= 2/3 * 4
y=4
x=8/3
y=4
x=2 ⅔
y=4
2/3x + 1¼y=9
x= 3/2y
2/3(3/2y) + 5/4y=9
x=3/2y
y+5/4y = 9
x= 3/2y
9/4y = 9 |: 9/4
x=2/3y
y=4
x= 2/3 * 4
y=4
x=8/3
y=4
x=2 ⅔
y=4
1/2x-2/4y=0×2
2/3x+11/4y=9
x=6/4y
2/3×6/4y+5/4y=9
x=6/4y
1 5/4y=9:9/4
x=6/4y
y=4
x=4×6/4
x=6
x=6
y=4
2/3x+11/4y=9
x=6/4y
2/3×6/4y+5/4y=9
x=6/4y
1 5/4y=9:9/4
x=6/4y
y=4
x=4×6/4
x=6
x=6
y=4